Parental origin of deletions and duplications - about the necessity to check for cryptic inversions - Liehr, Thomas; Schreyer, Isolde; Kuechler, Alma; Manolakos, Emmanouil; Singer, Sylke; Dufke, Andreas; Wilhelm, Kathleen; Jančušková, Tereza; Čmejla, Radek; Othman, Moneeb A K; Al-Rikabi, Ahmed H; Mrasek, Kristin; et al. (Molecular cytogenetics, 2018)
BACKGROUND: Copy number variants (CNVs) are the genetic bases for microdeletion/ microduplication syndromes (MMSs). Couples with an affected child and desire to have further children are routinely tested for a potential parental origin of a specific CNV either by molecular karyotyping or by two color fluorescence in situ hybridization (FISH), yet. In the latter case a critical region probe (CRP) is combined with a control probe for identification of the chromosome in question. However, CNVs can arise also due to other reasons, like a recombination-event based on a submicroscopic, cryptic inversion in one of the parents. RESULTS: Seventy-four patients with different MMSs and overall 81 CNVs were studied here by a novel three color FISH approach. The way how three locus-specific probes are selected (one is the CRP and two are flanking it in a distance of 5-10 Mb) enables to detect or exclude two possible parental conditions as origins of the CNV seen in the index: (i) direct parental origin of the CNV (deletion or duplication) or (ii) a parental cryptic inversion. Thus, for overall 51/81 CNVs (63%) a parental origin could be determined. 36/51 (70.5%) inherited the CNV directly from one of the parents, but 15/51 (29.5%) were due to an exclusively by three color FISH detectable parental inversion. A 2:1 ratio of maternal versus paternal inheritance was found. Also almost two times more male than female were among the index patients. CONCLUSION: The new, here suggested three color FISH approach is suited for more comprehensive parental studies of patients with MMS. The detection rate for parental origin was increased by 140% in this study. Still, for 30/81 cases (37%) no reason for the 'de novo' MMS in the affected index patient could be found by the here suggested FISH-probe set.
Keywords: Duplication; Deletion; Copy number variants (CNVs); Microdeletion/microduplication syndromes (MMSs); Three color fluorescence in situ hybridization (FISH); Inversion